Geology and Radiometric Survey of Tagima area, Northern Part of Adamawa Massif, Northeastern Nigeria - Ahmed, H. A.; Halilu, M.; Rufai, F.A.; Saleh, M.B (IJRDO-Journal of Applied Science, 2017)
Field mapping and radiometric reconnaissance survey of Tagima and environs was carried outwith the aim of producing geologic and isorad maps of the area and identifying possibleextension of uranium mineralization southwards from the popular Mika deposit. Geologic studyshows that the area is underlain by porphyritic granite, equigranular granite, migmatite andpegmatite. These rocks are characterized by joint and fault structures. Petrographic analysis ofthe porphyritic granite, equigranular granite, migmatite and pegmatite showed that theplagioclase, k-feldspars, biotite and quartz are the dominant minerals that constitute the rockunits. Radiometric survey shows high radiometric values in the northwestern, northeastern andsome of the southeastern parts of the area, while lower values are seen in the southern andsouthwestern parts. Analyses of the results shows high potentials for radioactive minerals inMika and Jasori areas, while low potential for radioactive minerals in southern part of Tagima area. While Mika area has already been established to have uranium deposits, possible extensionof radioactive minerals can be traced around Jasori and Tagima with decreasing potentialstowards southern parts of the study area.